STRATEGI BISNIS SYARIAH DALAM MENGHADAPI PANDEMI COVID-19 - Inayah Swasti Ratih (IZZI: Jurnal Ekonomi Islam, 2021)
This study aims to determine the strategies undertaken by businesses in the culinary sector in dealing with the Covid-19 Pandemic. The right strategy will lead businesses to survive the Pandemic. The business sector must be able to adapt to current world conditions, so there needs to be new strategies in business management. This study uses a qualitative research approach with field studies of culinary business actors in Bondowoso Regency. The results showed that the strategies undertaken by business actors were to make product innovation, improve service quality, read and capture digital opportunities, and adjust promotional materials. The strategies undertaken by business actors are able to keep business actors afloat during a pandemic.